Optimizing Company Resources for Sustainable Competitive Advantage: The Mediating Role of Digital Transformation in Indonesian MSMEs - Safina Najah Firdaussiah; Mohammad Riza Sutjipto; Saiful Hidayat (International Journal of Applied Business and International Management, 2026)
Micro, small, and medium (MSMEs) enterprises contribute crucially in this national economy, but there are always difficulties in transforming internal resources into sustainable competitive advantages in the digital era. This reseacrh aims to examine the “effect of company resources on competitive advantage, both directly and indirectly through digital transformation”. A quantitative approach was employed using data from 400 Indonesian MSMEs registered on the PaDi UMKM platform, analyzed from the SEM model or Structural Equation Modeling with LISREL 8.70. Resulting if company resources contributed significantly positively to competitive advantage (b = 0.15, t = 2.76) and on digital transformation (b = 0.71, t = 13.91). Digital transformation contribute strongly positively to competitive advantage (b = 0.66, t = 9.61), representing the most influential relationship in the model. Furthermore, the indirect effect of company resources on competitive advantage through digital transformation is significant (b = 0.469, t = 7.884), indicating partial mediation (VAF = 75.8%). The model explains 50% of digital transformation and 60% of competitive advantage, suggesting that digital transformation is the primary pathway through which resources translate into sustainable competitive advantage among MSMEs.